SEMIOTIKA SEBAGAI TEORI BARU DALAM PENAFSIRAN AL-QUR’AN: Aplikasi Teori Sastra Micheal Reffaterre - Husaini, Nurmala (Jurnal El-Hikam, 2021)
Recently, the methodology in the interpretation of the Koran has grown along with the guidance of the times and various epistemologies of thought that have developed, giving birth to different perspectives in interpreting texts. There are those who look for texts from a hermeneutic point of view that have contextual nuances and on the other hand there are those who change the text of the Al-Qur'an through a model approach (Al-Qur'an Semantics) which is oriented towards the literary aspects of the Al-Quran. The focus of this research examines a new study model in the interpretation of the Qur'an, namely the semiotic approach and step-by-step thinking (Micheal Reffaterre) now offers a new methodology and tools for interpreting the text of the Qur'an through the study of language (linguistics) that is capable of interpret both in terms of meaning and substance contained therein. So it can be denied that, the semiotic study in the al-Qur'an is in order to be able to understand the messages and language contained in the text.